Depósitos tecnogênicos na região noroeste de Goiânia (GO) - Dias, Marcel Bordin Galvão [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of techniques and complexity of society enabled to man the role of geological and geomorphological agent responsible for promoting changes in landscape. Human action on the environment results, among other manifestations, the formation of tecnogenic deposits, materials evidence of environment transformation by human activities, in particular urbanization. In urbanized environments, the genesis of deposits is related to the use model and occupation of soil existing and the form of appropriation relief compartments by different social groups. In certain areas, the poverty or lack of adequate infrastructure, such as urban drainage systems associated with land use without proper planning, promotes the remobilization of surface materials, resulting in the genesis of tecnogenic deposits and change in water dynamics, especially by the progressive grounding of floodplains. The geological-geomorphological action man produces several effects, especially in urban areas, which expands and diversifies, affecting, directly or indirectly, the population quality of life. This paper proposes to investigate the genesis of tecnogenic deposits in the northwest of Goiânia city, particularly in neighborhoods located in its south-central portion. Therefore, proceeded up the steps of environmental characterization of study area and field surveys to identify and collect tecnogenic materials. The materials were collected by inserting four-inch PVC bear witness, with meter long, pre-existing embankments in elected points for sampling. The sampling sites are located in flood plain areas or valley bottoms, preferred sites for sediments deposition and other materials transported by runoff flows, drainage channels and by direct deposition...

O desenvolvimento das técnicas e a complexificação da sociedade possibilitaram ao Homem o papel de agente geológico-geomorfológico, responsável por promover transformações na paisagem. A ação humana no ambiente resulta, dentre outras manifestações, na formação de depósitos tecnogênicos, materiais testemunhos da transformação dos ambientes pelas atividades humanas, em especial, a urbanização. Nos ambientes urbanizados, a gênese destes depósitos está relacionada ao modelo de uso e ocupação do solo vigente e à forma de apropriação dos compartimentos do relevo pelos diferentes grupos sociais. Em certas localidades, a precariedade ou inexistência de infraestrutura adequada, como os sistemas de drenagem urbana, associada à ocupação do solo sem o planejamento devido, promove a remobilização dos materiais superficiais, resultando na gênese de depósitos tecnogênicos e na alteração da dinâmica hídrica, especialmente pelo progressivo aterramento das planícies aluviais. A ação geológica-geomorfológica do Homem produz efeitos diversos, especialmente em áreas urbanas, na qual se amplia e diversifica, afetando, direta ou indiretamente, a qualidade de vida da população. Este trabalho propõe-se a investigar a gênese dos depósitos tecnogênicos na região noroeste da cidade de Goiânia (Goiás, Brasil), em particular, nos bairros situados em sua porção centro-sul. Para tanto, procederam-se as etapas de caracterização ambiental da área de estudo e levantamentos de campo para a identificação e coleta dos materiais tecnogênicos...
Keywords: Geografia; Paisagens; Geomorfologia ambiental; Geomorfologia - Goiania (GO); Geography